ANTI-QUORUM SENSING POTENTIAL OF LIMONIA ACIDISSIMA (L.) AGAINST VIBRIO HARVEYI KUMB-VA4 - P, Srinivasan; M, Rajalakshmi; Kumar S, Dinesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: This study aims to investigate the quorum-sensing inhibition (QSI) potential of Limonia acidissima L. against the biofilm forming Vibrio harveyi isolated from freshwater fish. Methods: The present study evaluated the anti-QS activity of the L. acidissima methanol and ethyl acetate (LA-M and LA-EA) fruit extracts using Chromobacterium violaceum ATCC 12472 (wild) and C. violaceum CV026 (mutant) as biomonitor strains and biofilm formation using the crystal violet assay. Vibrio sp. were isolated from freshwater-cultured fishes and screened for biofilm formation property. Strong biofilm forming isolate were subjected to molecular characterization. Limonia fruit pulp was subjected to methanol and ethyl acetate extraction using cold percolation method and yield was calculated. In parallel to determining the QSI properties of the extract, minimum inhibitory concentration (MIC), biofilm inhibition concentration (BIC), antibiofilm properties, and metabolic activity of LA-M and LA-EA against the biofilm forming V. harveyi KUMB-VA4 was determined. Results: The results of the present study demonstrated that the overall yield of methanol and ethyl acetate extract was 12.84% and 9.3% (w/w), respectively. Strong biofilm forming Vibrio isolate KUMB-VA4 was obtained from infected freshwater fishes and was subjected to molecular characterization. MIC of LA-M was 1510 Î¼g/ml and LA-EA was observed to be 3000 Î¼g/ml against the test pathogen, respectively. Biofilm inhibition assay revealed a BIC of LA-M at 250 Î¼g/ml and LA-EA at 500 Î¼g/ml. Both the plant extracts significantly reduced the biofilm formation of V. harveyi KUMB-VA4 and the metabolic activity in a dose-dependent manner. Light microscopy and scanning electron microscopy revealed that LA-M and LA-EA significantly altered 68.6% and 54.5% of the biofilm architecture at BIC. The QSI assay revealed that LA-M effectively reduced the violacein production of the biomonitor strains at sub-BIC (100â€“500 Î¼g/ml) to 80% than LA-EA (43%) in a strong dose-dependent fashion. Conclusions: The present study revealed the QSI property of Limonia acidissima against the biofilm forming V. harveyi isolated from infected fish.